2019
DOI: 10.1177/0954405419838384
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and simulation of surface topography machined by peripheral milling considering tool radial runout and axial drift

Abstract: Based on the Z-map model of a workpiece and the dynamic cutting forces model of peripheral milling in which the regenerative effect of tool radial runout and axial drift are considered, a model for the prediction of surface topography in peripheral milling operations is presented. According to the stability lobe diagram obtained by the zero-order analytical method, the relationship between spindle speed and surface topography, the tool radial runout, and the axial drift following the chatter are studied. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The Gaussian regression model was used to predict surface roughness of different machining parameters, and the accuracy rate was 84.3%. Chen [14] established the dynamic cutting forces model by considering the regeneration effect of tool run-out and axial drift, and proposed the surface topography simulation method based on the Z-map model. According to the zero-order analysis method, the stable cutting lobe diagram was obtained, and the surface roughness value near the resonance spindle speed and the left side of the lobe diagram was better.…”
Section: Introductionmentioning
confidence: 99%
“…The Gaussian regression model was used to predict surface roughness of different machining parameters, and the accuracy rate was 84.3%. Chen [14] established the dynamic cutting forces model by considering the regeneration effect of tool run-out and axial drift, and proposed the surface topography simulation method based on the Z-map model. According to the zero-order analysis method, the stable cutting lobe diagram was obtained, and the surface roughness value near the resonance spindle speed and the left side of the lobe diagram was better.…”
Section: Introductionmentioning
confidence: 99%
“…Manufacturing components with intricate profiles and low surface roughness using a hard-to-cut material is still a challenge. 18 The conventional machining process has countless limitations. Some of the most notable of these are related to macro-level material removal rate (MRR), tool wear rate, and material hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Chong et al 33 proposed an implicit four-order and three-step ADAMS numerical analysis method to solve the milling dynamic differential equation, which provided the optimization method of cutting parameters for circular corner milling. Chen et al 34 employed a model to predict the surface morphology of peripheral milling based on Z-map model and dynamic cutting force model of peripheral milling considering regeneration effect. It was found that when the frequency of the milling system was an integral multiple of the machining frequency, a stable cutting state coul be obtained but the surface finish was poor.…”
Section: Introductionmentioning
confidence: 99%